2012
DOI: 10.1186/1471-244x-12-179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep disturbance on patients in treatment for mental disorders

Abstract: BackgroundIn clinical practice, sleep disturbance is often regarded as an epiphenomenon of the primary mental disorder. The aim of this study was to test if sleep disturbance, independently of primary mental disorders, is associated with current clinical state and benefit from treatment in a sample representative of public mental health care clinics.Method2246 patients receiving treatment for mental disorders in eight public mental health care centers in Norway were evaluated in a cross-sectional study using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…Previous research on sleep disturbance has indicated that specifically targeted sleep interventions are a pre‐requisite in order to significantly improve insomnia (Kallestad et al ., ). Our results, however, show that the patients with pre‐treatment sleep disturbance had a significant reduction in sleep problems from pre‐treatment to post‐treatment, and that these improvements were maintained at follow‐up.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research on sleep disturbance has indicated that specifically targeted sleep interventions are a pre‐requisite in order to significantly improve insomnia (Kallestad et al ., ). Our results, however, show that the patients with pre‐treatment sleep disturbance had a significant reduction in sleep problems from pre‐treatment to post‐treatment, and that these improvements were maintained at follow‐up.…”
Section: Discussionmentioning
confidence: 97%
“…Despite these findings, little is known about whether sleep disturbances influence treatment outcome when the patients receive adequate psychological treatment for their OCD-problems, or if comorbid sleep disturbances are affected when the OCD is effectively treated. Although studies indicate that secondary sleep disturbances are improved when the primary disorder is treated (Harvey, 2001), research also suggest that sleep disturbances should be specifically targeted during treatment in order to be successfully treated (Kallestad, Hansen, Langsrud et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, a good sleep may be considered as a strong predictor of a good health,6,7 and conversely, a disturbed and/or interrupted sleep would be accompanied by many alterations in all aspects of life, in both genders and at all ages 8,9. In fact, sleep plays a key role for daytime functioning and neurocognitive performance in childhood and adolescence,10 probably promoting and/or influencing the neural plasticity process and enhancing memory consolidation during life 11.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from our research demonstrates that day-to-day variability in sleep-wake cycles is associated with longer duration of acute psychiatric admissions and frequency of aggression or violent incidents [6,7]. Lastly, sleep problems are often the last symptoms to resolve during recovery from an acute episode of a mood or psychotic disorder [8,9]. Overall, experimental and clinical research emphasize the reciprocal relationship between sleep-wake disruptions and mental disorders showing that they perpetuate and exacerbate each other and that improved sleep is associated with improvements in mental state [10][11][12][13].…”
Section: Introductionmentioning
confidence: 84%